1.1‐Millimeter Tall Vertically Aligned‐Carbon Nanotubes Grown by Cold Wall CVD Using a Novel Multiple‐Purge Method. Issue 20 (2nd June 2022) - Coelho, Cláudia; Machado, George
Abstract: This paper reports a multi‐phase deposition for the growth of carbon nanotubes, intercalating phases of effective growth with purges of the reactor, based on the method recently proposed by the author to grow tall vertically aligned carbon nanotubes (VA‐CNT) in a cold‐wall system at low pressure. The test performed consists on running several growths varying the number of cycles during the deposition step and their duration, avoiding a massive study of number of cycles in function of the time and vice versa. The goal here is to verify if the chamber reconditioning and the purge cycles contribute to increase the height and the uniformity of the VA‐CNT forests. The maximum height achieved is 1.1 mm for 11 cycles, in a total time of 110.5 min, with a non‐uniformity of 6.0% under 6.8 Torr. The analysis of the saturation of the deposition is registered around 127 min. Abstract : This paper opens opportunities for research laboratory to grow tall‐carbon nanotubes in the cold wall chemical vapor deposition (CVD) system. This study is based on the low‐pressure work which is more difficult than atmospheric to grow taller carbon nanotubes. These results allow 1 mm tall carpet of carbon nanotube without any support accessories used currently for hot‐wall chemical vapor deposition system.